Multilevel Shoe Rack - Sabaruddin, Muhammad Aizat Zulkarnain; Suhaimi, Muhammad Aleef Aiman; Rosdi, Wan Nuralya Afrina; Mohamad, Mahmod Abd Hakim; Mat Zian @ Mat Zin, Ahmad Faiz; Asril Rajo Mantari, Muhammad Hanafi (Multidisciplinary Applied Research and Innovation, 2025)
A shoe rack is essential furniture for organizing footwear at home or in the workplace. The Multilevel Shoe Rack was developed to address the difficulties faced by individuals with osteoarthritis when wearing shoes. The main objective of this project is to design and fabricate a multipurpose shoe rack that can store up to 12 pairs of shoes while also serving as a seating bench. Constructed primarily from chipboard for its affordability and adequate strength, the rack features a three-layer flip frame hinge system, creating three storage sections. To enhance comfort, faux leather and sponge are used as a seat cover. Test results demonstrated that the rack not only accommodates 12 pairs of shoes neatly but also supports the weight of two adults sitting simultaneously.